Similar expression of oxidative genes after interval and continuous exercise - Wang, L.; Psilander, N.; Tonkonogi, M.; Ding, S.; Sahlin, K. (Medicine & Science in Sports & Exercise, 2009)
Purpose: There is a debate whether interval or traditional endurance training is the most effective stimulus of mitochondrial biogenesis. Here, we compared the effects of acute interval exercise (IE) or continuous exercise (CE) on the muscle messenger RNA (mRNA) content for several genes involved in mitochondrial biogenesis and lipid metabolism.